2023
DOI: 10.1002/art.42627
|View full text |Cite
|
Sign up to set email alerts
|

Gut Inflammation in Axial Spondyloarthritis Patients is Characterized by a Marked Type 17 Skewed Mucosal Innate‐like T Cell Signature

Abstract: ObjectiveSpA patients often present with microscopic signs of gut inflammation, a risk factor for progressive disease. We investigated whether mucosal innate‐like T‐cells are involved in dysregulated interleukin (IL)‐23/IL‐17 responses in the gut‐joint axis in SpA.MethodsIleal and colonic intraepithelial lymphocytes (IEL) and lamina propria lymphocytes (LPL), and paired peripheral blood mononuclear cells (PBMC), were isolated from treatment‐naive non‐radiographic axial (nr‐ax)SpA patients with (n=11) and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A similar enrichment in the inflamed joints of patients with SpA of IL-17-producing innate-like T cells provides support for the existence of a "gut-synovial axis" (2,4). Intestinal dysbiosis, an imbalance of the microbiota, leads to increases in intestinal permeability, which has been implicated in the pathogenesis of several autoimmune conditions, such as type I diabetes, celiac disease, and inflammatory bowel disease (8).…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…A similar enrichment in the inflamed joints of patients with SpA of IL-17-producing innate-like T cells provides support for the existence of a "gut-synovial axis" (2,4). Intestinal dysbiosis, an imbalance of the microbiota, leads to increases in intestinal permeability, which has been implicated in the pathogenesis of several autoimmune conditions, such as type I diabetes, celiac disease, and inflammatory bowel disease (8).…”
mentioning
confidence: 78%
“…Furthermore, we have shown that, although IFN γ-producing iNKT cells are protective against severe arthritis development in SKG mice, over time, the increased prevalence of NKT17 cells in the arthritic joints and draining lymph node positively correlates with disease severity (18). Unlike in synovial fluid, iNKT cells are too infrequent in the intestine of the patients with SpA to characterize them for transcription factor expression or function (2). Like γδT cells, MAIT cells in the intestine also are affected in patients with nonradiographic axial SpA (2), and increases in MAIT cells are found in synovial fluid of patients with SpA and patients with rheumatoid arthritis (19).…”
mentioning
confidence: 99%
See 2 more Smart Citations